Nonsense and the General Form of the Sentence - Michael Morris (Public Reason, 2025)
In his paper ‘The Bounds of Nonsense’ Adrian Moore defines sentences for Wittgenstein’s Tractatus as those items to which truth-operations apply, and understands this as a disjunctivist theory. I consider whether this view can plausibly be attributed to Wittgenstein, whether it is compatible with the way Wittgenstein draws the distinction between propositions (narrowly construed) and nonsensical pseudo-propositions, and whether it is compatible with the more general philosophy of the Tractatus. Understanding the Tractatus in the way suggested by the disjunctivist definition of sentences transforms the way we read the text.